Social anxiety and MDMA-assisted therapy investigation: a novel clinical trial protocol - Lear, M. Kati; Smith, Sarah M.; Pilecki, Brian; Stauffer, Chris S.; Luoma, Jason B. (Frontiers in Psychiatry, 2023)
Background: Social anxiety disorder (SAD) is a serious and prevalent psychiatric condition that heavily impacts social functioning and quality of life. Though efficacious treatments exist for SAD, remission rates remain elevated and a significant portion of those affected do not access effective treatment, suggesting the need for additional evidence-based treatment options. This paper presents a protocol for an open-label pilot study of MDMA-assisted therapy (MDMA-AT) for social anxiety disorder. The study aims to assess preliminary treatment outcomes, feasibility and safety, and psychological and physiological processes of change in the treatment of SAD with MDMA-AT. A secondary aim includes the development of a treatment manual for MDMA-AT for SAD. Method: The outlined protocol is a randomized, open-label delayed treatment study. We will recruit 20 participants who meet criteria with moderate-to-severe social anxiety disorder (SAD) of the generalized subtype. Participants will be randomly assigned to an immediate treatment (n = 10) or delayed treatment condition (n = 10). Those in the immediate treatment condition will proceed immediately to active MDMA-AT consisting of three preparation sessions, two medicine sessions in which they receive oral doses of MDMA, and six integration sessions over approximately a 16-week period. The delayed treatment condition will receive the same intervention after a 16-week delay. Our primary outcome is SAD symptom reduction as measured by the Liebowitz Social Anxiety Scale administered by blinded raters at post-treatment and six month follow up. Secondary outcomes include changes in functional impairment, feasibility and safety measures, and novel therapeutic processes of change including shame and shame-related coping, belongingness, self-concealment, and self-compassion at post-treatment. Exploratory outcomes are also discussed. Discussion: The results of this pilot trial advance the field’s understanding of the acceptability and potential effectiveness of MDMA-AT for social anxiety disorder and provide an overview of relevant therapeutic mechanisms unique to SAD. We hope findings from this protocol will inform the design of subsequent larger-scale randomized controlled trials (RCT) examining the efficacy of MDMA-AT for SAD.